O trabalhar dos profissionais dos serviços gerais de limpeza hospitalar: uma análise da relação trabalho- saúde - Silva, Flávia Marcelly de Sousa Mendes da (2017)
The aim of this dissertation is to analyze the relationship between work and health of the professionals of general hospital cleaning services of an University Hospital in a capital city in northeast of Brazil. From a theoretical point of view, the Psychodynamics of Work and the Ergonomics of Activity are the main approaches used to analyze the complex relationships between work and health. As for method, a qualitative approach was chosen, which had as instruments a semi-structured individual interview (based on a script built from the theoretical categories of the research) and a sociodemographic questionnaire. The collected dada were analyzed using Iramuteq software. The sample consisted of 30 hospital cleaning servers, ranging from 21 to 61 years (M = 40.3, SD = 11.0), single (43.3%), female (66.7%), Incomplete secondary education (50%). The length of service ranged from three days to 28 years in the researched organization. From the analysis of the Hierarchical Describing Classification, the corpus was divided into five classes that were named from their most representative descriptors: Risks at Work, Training and Professional History, Working Conditions, Suffering at Work, and Strategies of Defense and Organization of the Job. Regarding the results, it was verified that cleaning servers are exposed to risks in their work environment, being these physical, chemical and biological, resulting from several situations of vulnerability, among which were identified infectious, musculoskeletal problems; As well as psychic issues such as anxiety, stress, sleep disorders, and emotional exhaustion. Regarding the history and professional training, it was verified that majority have low professional qualification, being this the first job of signed portfolio. They appear as previous jobs: hourly housekeeper, day laborer, waiter and housekeeper. It also identifies deficient training that generates anxiety and insecurity in the servers. As regards working conditions, there was a lack of safety equipment (e.g., glove, mask and hat), inappropriate furniture that exposes workers to hazardous situations and affects the health of these workers. As sources of suffering at work, the conflictual relationship with leadership, invisibility and prejudice became evident. However, the feeling of usefulness in the maintenance of hospital cleaning and janitorial care, the relationship with the peers and even the salary issue were found as sources of pleasure. The praise given by users, patients extol the sense of usefulness and thus, transform suffering into pleasure at work. Last but not least, the organization of work through strict supervision of the bosses, control of time, movements and breaks, as well as the high workload, stands out as an important source of suffering. In this way, it is sought, through the results of this study, to contribute to the production of knowledge regarding the health of hospital cleaning servers, opening the possibility of future transformations of this reality.